2007
DOI: 10.1002/app.26243
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of LLDPE‐NR reactive blending with maleic anhydride

Abstract: A binary blend and ternary reactive blends of 90/10 LLDPE/NR using maleic anhydride (MA) as a reactive agent with and without dicumyl peroxide (DCP) were made at 1508C in an internal mixer. The fracture surfaces of the blends were conventionally observed by TEM and atomic force microscope, revealing that the rubber domains became smaller with the addition of MA and DCP. This suggested that the in situ graft copolymer (LLDPE-g-NR) was formed and acted as an in situ compatibilizer to enhance interfacial adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Although TPVs prepared from blends of polyethylene and natural rubber have been studied by various research groups,3, 7–16 the specific high molecular weight and presence of impurities contraindicates the use of natural rubber either in the blends or in the thermoplastic elastomer vulcanizates. The special viscoelastic properties of natural rubber, combined with the dynamic properties of vulcanizate HDPE/NR, improved the energy absorption characteristics during cyclic deformation, suggesting the suitability of the material for use as a vibration damper for aerospace applications 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TPVs prepared from blends of polyethylene and natural rubber have been studied by various research groups,3, 7–16 the specific high molecular weight and presence of impurities contraindicates the use of natural rubber either in the blends or in the thermoplastic elastomer vulcanizates. The special viscoelastic properties of natural rubber, combined with the dynamic properties of vulcanizate HDPE/NR, improved the energy absorption characteristics during cyclic deformation, suggesting the suitability of the material for use as a vibration damper for aerospace applications 7.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a phenolic modified polyethylene compatibilizer increased the dispersion of the vulcanized rubber domains in the HDPE matrix, resulting in enhancement of the mechanical properties with respect to tensile strength and elongation at break, as well as dynamic properties. In addition, Magaraphan et al16 studied the morphology of binary and ternary reactive blends (in the ratio of LLDPE/NR = 90/10) using maleic anhydride as a reactive agent with and without the admixture of dicumyl peroxide (DCP). This finding suggested that an in situ graft copolymer of LLDPE‐ g ‐NR was formed, acting as an in situ compatibilizer in this blend system, with reduction of rubber domains corresponding with the addition of DCP.…”
Section: Introductionmentioning
confidence: 99%
“…When organoclay particles were later incorporated, their dispersion would be improved as a result of interaction between the MA carbonyl and the clay silanol group, promoting the carbonyl‐silanol interface interaction with the formation of hydrogen bonds 27. In general, MA is used as a reactive reagent to enhance the compatibilization of LLDPE and rubber phase 9. This would reduce the energy barrier and therefore enhance interphase miscibility.…”
Section: Resultsmentioning
confidence: 99%
“…The studies showed that the polymer–filler interactions and mean agglomerate particle size of dispersed phase have a significant influence on the mechanical properties of samples 8. Magaraphan et al9 have studied the effects of the maleic anhydride (MA) as a compatibilizer on the morphology of LLDPE/NR blends and showed that the in situ copolymer is capable of promoting good interfacial adhesion, consequently enhanced mechanical properties. Moreover, the copolymer containing fine fibrils and more links between domains plays a key role in inducing compatible blends 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation